1994
DOI: 10.1093/ije/23.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Mortality and Coronary Heart Disease between Lithuania and the Netherlands: Results from the WHO Kaunas-Rotterdam Intervention Study (KRIS)

Abstract: The results provide evidence for geographical differences in mortality and morbidity between Lithuania and the Netherlands. Population-specific health behaviours were shown to be involved in differences in the risk of CHD. The lower CHD rates in Eastern European communities in the 1970s, in this study confirmed for Lithuania, suggests that the apex of the CHD epidemic had not yet reached the Lithuanian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is in agreement with the World Health Organisation's monitoring trends and determinants in cardiovascular disease study (MONICA) performed in 1983-6, which showed that Lithuanian men from Kaunas had higher body mass index and moderately higher systolic blood pressure than Swedes from Gothenburg, whereas plasma cholesterol concentrations and smoking habits were similar 23. In addition, the Kaunas-Rotterdam intervention study showed that in 1972-4 Lithuanian men had a more advantageous cardiovascular risk profile with less smoking, lower cholesterol concentration, and higher rates of physical activity than Dutch men 5. Obviously, data from these two studies could not predict the dramatic increase in mortality from coronary heart disease in Lithuania over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with the World Health Organisation's monitoring trends and determinants in cardiovascular disease study (MONICA) performed in 1983-6, which showed that Lithuanian men from Kaunas had higher body mass index and moderately higher systolic blood pressure than Swedes from Gothenburg, whereas plasma cholesterol concentrations and smoking habits were similar 23. In addition, the Kaunas-Rotterdam intervention study showed that in 1972-4 Lithuanian men had a more advantageous cardiovascular risk profile with less smoking, lower cholesterol concentration, and higher rates of physical activity than Dutch men 5. Obviously, data from these two studies could not predict the dramatic increase in mortality from coronary heart disease in Lithuania over the past 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…shows an example of these trends in middle aged men in Lithuania and Sweden. The generally held view is that traditional risk factors for coronary heart disease–that is, high blood pressure, smoking, and dyslipidaemia–have the same predictive strength in eastern and western Europe and could explain these differences in mortality 5. However, other factors may also be important.…”
Section: Introductionmentioning
confidence: 99%